DIAGNÓSTICO DAS FORMAS DE USO E OCUPAÇÃO DO ESPAÇO URBANO DO MUNICÍPIO DE JACINTO MACHADO (SC) - Marcelino, Emerson Vieira (Caminhos de Geografia, 2003)
The integrated project of research "Environmental Quality of the South Region of Santa Catarinaâ€? linked to the Departament of Geoscience/UFSC has as objective to elaborate recommendations and relative propositions to the management of the area quality life. The third phase of this project was centralized in the Timbé do Sul and Jacinto Machado counties, both located in Araranguá (SC) region. Thus, as an integral part of the environmental diagnosis of the Jacinto Machado, this study focused on contemplating the land use and occupation of the urban area. Three main aspects were considered: colonization model, the formation agents and environmental problems issues.